KONSONANSI KONGNITIF SISWA TENTANG PERAN GURU DAN DAMPAKNYA TERHADAP PENYESUAIAN SISWA DI SEKOLAH DASAR : Penelitian Pada SMA Negeri Dan Swasta Di Kodya Bandung - Sofyan S. Willis, - (1992)
SMA students who are in late adolescence, with the characteristic of intellectual, social, and emotional maturity, are very potential to develop. Evidence are easily found, in the forms of ideas and achievements, both in intra and extra curricular activities. This should be taken into account in the effort of guidance and counseling in schools, in order that the students are independent, creative, and productive, to anticipate problems in rapid social and global change. The developmental approach in guidance is more suitable for students development. However, there are still many school counselors are using therapeutic approach, because they merely view it from the point of view of students' maladjustification. It is true that there are evidence of maladjustifications among small number of students such as fighting, alcoholic drink, drug abuse ect, but there are more evidence of students' potency in the academic and extracurricular fields: art and culture, sports, science and technology, leadership, jounalistic, etc. Guidance cannot be separated from education as the process of socio-cultural tansformation to help individuals become independent, creative, and productive. To meet the objectives, the awareness or self understanding is needed, and should be in conducive situation as to help individuals develop his capacity. Guidance is an effort to help student through conducive situation with the counselors' personality and skill's `32; to achieve self understanding and self direction in order that the student develop his independence and self actualization. In other words, guidance is the core of education. The guidance units have not been able to do much to help students develop their potentiality. The constarins are: (1) big amount of student in each class, compared with limited amount of scool counselors available; (2) school counselors are too much involved in teaching, so they have not enough time to work on guidance and counseling based on student's need, aspiration, and their social-cultural life; (3) most students who are facing problems have little interest in asking for help guidance available in schools, because they feel indefference, shy and scared. Persumable is due to the lack of school counselors professional. Waiting untill they arranging the guidance in schools, this study sees teachers' role in guidance, because (1) we relatively have many teachers, (2) techers have enough time to communicate with students, and (3) there are many students who want the help of teachers. The key to the implementation of the teachers' role is teachers' quality in the student-teacher relationship. Academic orientation in formal education makes teachers so busy with teaching, that counseling for the sake of student's personality development is neglected. Students have potentiality, their own future and individual problems as well. To meet the need, the role of ideal teachers (in counseling and teaching ) is badly needed. The role of ideal teachers is student's hope, so that it becomes an important element in their cognition. If the teachers can play their role in accordance with the students'hope, the cognitive consonance of the students will occur. This study tries to see the students social adjustment from the point of view of students' cognitive consonance about the role of the teacher, in student-teacher relationship. The main question of this research is, "Does student's cognitive consonance about teachers' role really happen, and how does it happen ? What is the influence of student^s cognitive consonance to student"s social adjustment?" This research uses descriptive analysis method, and the respondents are state and private high school students in Bandung. The result of data analysis is interpreted and affirmed with data analysis resulted from interview and observation. The result of the research shows that most of the students (75,55%) experienced cognitive consonance about teachers' role, (24,45%) experienced cognitive dissonance. Students' cognitive consonance contributes positive impact on the students' social adjustment in schools. It can be concluded, therefore, that through the conitive cosonance effort enables students' social adjustment posively. The finding of this research is "The Concept of Student Social Adjustment Development through Student Cognitive Consonance". This concept is the concept of guidance and counseling.